Cascade‐ and Orthoamide‐Type Overman Rearrangements of Allylic Vicinal Diols. Issue 36 (19th July 2013) - Nakayama, Yasuaki; Sekiya, Ruriko; Oishi, Hiroki; Hama, Naoto; Yamazaki, Miki; Sato, Takaaki; Chida, Noritaka
Abstract This article describes the details of two new types of Overman rearrangement from allylic vicinal diols. Starting from identical diols, both bis(imidate)s and cyclic orthoamides were selectively synthesized by simply changing the reaction conditions. Whilst exposure of the bis(imidate)s to thermal conditions initiated the double Overman rearrangement to introduce two identical nitrogen groups in a single operation (the cascade‐type Overman rearrangement), the reaction of cyclic orthoamides resulted in a single rearrangement (the orthoamide‐type Overman rearrangement). The newly generated allylic alcohols from the orthoamide‐type reaction can potentially undergo a variety of further transformations. For instance, we demonstrated an Overman/Claisen sequence in one pot. The most conspicuous feature of this method is that it offers precise control over the number of Overman rearrangements from the same allylic vicinal diols. This method also excludes the tedious protecting‐group manipulations of the homoallylic alcohols, which are necessary in conventional Overman rearrangements. All of the performed rearrangements proceeded in a completely diastereoselective fashion through a chair‐like transition state.